Early Warning and Physical Education Intervention of Psychological Crisis among College Students Based on Artificial Neural Network - Qiuxiang Shi; Qianqian Yang; Ning Cai (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The development of modern society has complicated the learning and living environment of college students, which induces significant psychological problems. However, most scholars focus on quantitative evaluation based on objective survey and statistical analysis, or contrastive experiments based on predesigned intervention methods. Few of them consider the interaction between influencing factors, and judge the degree of psychological crisis reliably. To solve the problem, this paper introduces artificial neural network (ANN) to the early warning and physical education (PE) intervention of psychological crisis among college students. Based on a reasonable index system, the psychological crisis of college students was studied with the structural equation, considering the interaction effect between influencing factors. Next, a bidirectional long short-term memory (BiLSTM) network was constructed for the analysis on the psychological crisis of college students, and the degree of psychological crisis of college students was evaluated, with the aid of emotional labeling attention mechanism. Finally, the effect of PE intervention on psychological stress easement of college students was discussed in details. The proposed method was proved valid through experiments.